2006
DOI: 10.1097/01.ccm.0000190622.02222.df
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin-induced heart dysfunction in rats: Assessment of myocardial perfusion and permeability and the role of fluid resuscitation*

Abstract: Endotoxin can induce reversible myocardial alterations with evidence of coronary hypoperfusion and heart wall enlargement/damage, some of which can be prevented by fluid resuscitation. The use of crystalloids is less beneficial than pentastarch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 40 publications
2
29
1
1
Order By: Relevance
“…74 On the other hand, myocardial ischemia in susceptible areas is induced by NO inhibition, hence reducing coronary blood flow. 75 Overall, any mismatch of perfusion to oxygen consumption ratio occurring in septic patients is liable to induce patchy microareas of myocardial damage with troponin I release, 76 because of the limited available myocardial oxygen extraction reserve.…”
Section: The Heart In Sepsismentioning
confidence: 99%
“…74 On the other hand, myocardial ischemia in susceptible areas is induced by NO inhibition, hence reducing coronary blood flow. 75 Overall, any mismatch of perfusion to oxygen consumption ratio occurring in septic patients is liable to induce patchy microareas of myocardial damage with troponin I release, 76 because of the limited available myocardial oxygen extraction reserve.…”
Section: The Heart In Sepsismentioning
confidence: 99%
“…Moreover, animal studies and human observations [6][7][8] have indicated that myocardial dysfunction occurs globally. Sepsis-related myocardial dysfunction does not relate to myocardial ischemia or necrosis but is associated with cytokine-induced myocardial depression [5] and myocardial oedema, the later due to increased vascular permeability and leakage [9,10]. In sepsis both systolic and diastolic bi-ventricular myocardial dysfunction may be present [1,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Figura 1. los mecanismos que explican la disfunción miocárdica durante la sepsis son múltiples y probablemente actúan sinérgicamente para dar origen a las manifestaciones clínicas propias de esta disfunción, siendo la más característica la disminución de la fracción de eyección del ventrículo izquierdo. Cambios micro-circulatorios La inflamación microvascular se asocia a edema intersticial miocárdico y compromiso directo de las fibras contráctiles, que contribuyen a la caída de la distensibilidad y función miocárdica 7,38 . Aunque el flujo coronario está aumentado en la sepsis, el flujo microcirculatorio parece estar afectado por edema endotelial y depósitos de fibrina que enlentecen u obstruyen el flujo microvascular 39 .…”
Section: Inflamaciónunclassified